An Improved Wu-Manber Multiple Patterns Matching Algorithm for Mobile Internet Content Security Audit in a Chinese Environment - Zhang, Zhenjiang; Jin, Xinlei; Hao, Ziqi; Guan, Xiaolan (International Journal of Security and Its Applications, 2014)
The rapid progress of mobile Internet has brought about wide range of applications of security audit systems. As a part of security audit system, content security audit is crucial for ensuring the reliability and security for system applications. In this paper, we propose a novel multiple patterns matching algorithm WMMA based on the Chinese context (Wu-Manber Algorithm for Mobile Internet Security Audit) to realize auditing the interactive content in the mobile Internet. Our improved algorithm based on the efficient WM (Wu-Manber) multiple patterns matching algorithm, which can improve the insufficient of the WM when dealing with Chinese context. The simulation results showed that the improved algorithm is more suitable for the mobile Internet content security auditing of Chinese language environment, which has higher operation efficiency.